Pengaruh Pendekatan Konstruktivisme Berbantuan Alat Peraga “BARETRIKA” Terhadap Motivasi dan Hasil Belajar Matematika Siswa Kelas X Perhotelan SMK Negeri 2 Kota Kediri - Cahyaningtyas, Yusti Ayu; Nurfahrudianto, Aan; Handayani, Aprilia Dwi (Peneliti.net, 2025)
Education is an important aspect of life, and issues in the education system need to be addressed, such as teaching efficiency and teacher welfare. The Freedom to Learn Program is the government’s effort to improve the quality of education by prioritizing freedom in learning. Teachers have a key role in creating an effective learning environment, especially in abstract subjects such as mathematics. This research aims to increase students’ motivation and mathematics learning outcomes through a constructivist approach using the “BARETRIKA” teaching aids. The research method used is experimentation with a quantitative approach. The research results showed a significant increase in student motivation and learning outcomes after implementing the constructivism approach. Therefore, this approach can make a positive contribution to mathematics learning at SMK Negeri 2 Kediri City.